(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the article of the natural populations of the Jalal-Abad and Naryn regions, the reserves of the dye macrotomy - Macrotomia euchroma (Royle) Pauls were first determined. And the immortality of Samarkand - Helichrysum maracandicum Popov Ex Kirp. Studies on biological and operational reserves of two types were conducted, distribution areas and annual billet limits were compiled. The area of macrotomy of coloring in the Jalal-Abad region is 42.5 hectares with a total biological supply of roots of 33.39 tons in dry form. Operational supply - 16.7 tons. In the Naryn region, the macrotomy of coloring on an area of 1585 hectares was established. The biological reserve is 739.6 tons, operational - 369.8 tons. The habitat of the immortality of Samarkand in the Chatkal Valley of the Zalal -Abad region, suitable for harvesting drug raw materials, is estimated at 1000 hectares, where the biological supply of dry inflorescences is 150 tons, and the operational - 100 tons .